Application of a matrix converter in a slip energy recovery drive system - Altun, Hüseyin (My University, 2005)
This paper describes speed control of wound-rotor induction motor using the slip energy recovery principle. The proposed drive system uses a matrix converter to extract the slip energy from the rotor into the mains instead of using converter cascade. The system enables the motor to be operated at both subsynchronous and supersynchronous regions. Comprehensive simulation results are given to demonstrate transient and steady state operation of the drive system.
Keywords: Drive system; Matrix converter; Slip energy recovery principle; Wound-rotor induction motor